Detailed Identification of the Progression of Antiphase Boundaries in GaP/Si(001). (22nd October 2019) - Farin, Pascal; Marquardt, Malte; Martyanov, Wjatscheslav; Belz, Jürgen; Beyer, Andreas; Volz, Kerstin; Lenz, Andrea
Abstract : We present a detailed analysis of two-dimensional defects arising at the interface of the nonpolar semiconductor Si to the polar III/V-semiconductor GaP. These defects consist of so called wrong bonds, i. e. two of the same atoms bound to one another. On the two different sides of the defect, the polarity of the GaP crystal is flipped. Accordingly, the defects are called antiphase boundaries. They occur regularly during growth of polar semiconductors onto nonpolar substrates [1] and form three-dimensional antiphase domains investigated in this work.